Investigating Light and Water Optimization for Early Seedling Establishment in Albizia lebbeck (L.) Benth - Kelechi Godwin Ibeh; Adejoke Olukemi Akinyele (South-East European Forestry)
Seedling growth, development, and establishment are vulnerable stages for trees, greatly influenced by two important environmental factors: light availability and soil moisture regime. This study investigated the interactive effects of light intensity and water availability on key early vegetative growth parameters of collar diameter, height, and the number of leaves in seedlings of the tropical legume tree Albizia lebbeck. The experiment utilized a 4×3 factorial design with four light intensity levels (L1 (75%), L2 (50%), L3 (25%), and L4 (100% as control)) and three watering frequencies (daily (W1), every three days (W2), weekly (W3) in a nursery greenhouse. Measurements were recorded biweekly for ten weeks. The results showed that moderate light intensity of 50% coupled with adequate moisture supply by daily watering (L2W1) led to optimal seedling growth. This treatment combination resulted in the greatest mean collar diameter (3.62 mm), plant height (41.88 cm), and number of leaves (11). Growth was restricted under full light (L4) and insufficient light (L3). Limited water availability by watering weekly (W3) also suppressed growth metrics. However, there was no significant difference between daily watering (W1) and moderate watering frequency (W2). Strong intrinsic synchronization was observed between the collar diameter and plant height growth trajectories over time, reflecting coordinated lateral and vertical stem expansion regulated by developmental processes. Leaf proliferation showed partially decoupled dynamics from stem growth, indicating specialized control over leaf traits. Collar diameter, height, and the number of leaves were inherently intercorrelated, highlighting their co-dependence in generating resources and signals needed to sustain growth and development. The findings suggest that 50% light intensity and adequate moisture by watering every 1-3 days are optimal for nursery establishment of A. lebbeck seedlings to maximize early vegetative growth.